Examining EFL Teachers' Perspectives: Enhancing Learning Through Technology-Integrated Instruction - Marsevani, Maya; Sasmi, Nafa Indah; Zaki, Leil Badrah (Linguists : Journal of Linguistics and Language Teaching, 2024)
This study aims to examine EFL teachers' perspectives on improving learning by integrating learning with technology. This research utilized a qualitative case study methodology. Data collection was conducted using a combination of observation and in-depth interviews. Observations provided direct insight into the classroom environment, while interviews allowed teachers to share their perspectives and experiences regarding technology integration. The participants of this study were two purposively selected English teachers from a public secondary school in Batam City, each of whom had more than five years of experience in integrating technology into their teaching practices. The findings showed that technology integration significantly increased students' motivation and engagement, facilitating a more dynamic learning environment. Teachers reported that multimedia resources, interactive apps, and authentic language materials improved language proficiency and fostered important skills such as digital literacy and problem-solving. In addition, this study highlights the importance of flexibility and adaptability in teaching strategies, as teachers have to face technical challenges and adjust their lesson plans accordingly.